(3eYLes
(3ChdgG (B:s
(3J (B: (3GdHMJ GdUQa jbGd TQGH HMJ Ci QLd KHJ GdLfGf Ci KHJ GdbdH s
(3BNQgG (B:s
(3BNQ GdehLhO efgG (B:(3bhdg (B: (3d (B: (3jbGd (B: (3eGdi bO YedI Ci TF hGdbO YedI ef GdfSGA GdNSjSI GdbUjQI J (B: (3GdNHYKfI GdCSO GdTOjO hcPG ai GdQLGd s
(3JHY GdeHJhQ ai hQbI (B24 (3H (B: (3HGH aYd HVe GdaGA hJScjf GdYjfs
(3cJHJ HNW bdjd GdfbWs
(3cJHJ YfhGfGJgG HGdMeQIs
(3eQJH Ydi GdChRGf hJOQL GdMQha GdCHLOjI ai BNQ GdhRf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GddZIs